A Proposed Arabic Monolingual Web-Based Terminology Management System. Issue 1 (2nd June 2022) - Eid, Sherine
Abstract: Arabic controlled vocabularies do not differ from all other controlled vocabularies as far as basic features are concerned, however they do bear a number of shortcomings, which have limited their effectiveness dissemination. These include the lack of adaptations to Arab-specific applications, and the failure of terms to connote the content of subject areas easily and consistently. Besides, differences and variability in terminology and syntax cause problems in cross-domain or cross-system interoperability. In addition, Existing software is unequipped to service Arabic-speaking libraries in such a way that allows them to be technologically comparable with modern libraries around the world, thus limiting their integration into the international library community. This technological shortcoming also limits the ease by which they are able to make knowledge resources attainable to researchers and other library users. This article proposes a framework for a monolingual web-based terminology management system that operates in Arabic and supports the use of Arabic controlled vocabularies. This article is based on ISO 26162:2012 Systems to manage terminology, knowledge and content — Design, implementation and maintenance of terminology management systems.